Analisis angin zonal dan outgoing longwave radiation (OLR) untuk inisialisasi kemunculan fenomena madden julian oscillation (MJO) di Kota Padang - Delvita Handayani (PILLAR OF PHYSICS, 2016)
Maden Jullian Oscillation (MJO) is the most dominant climate variations occur in the equatiorial region and was centered in the Indian ocean and the Pacific ocean which affects the climate change. This research was conducted to determine the pattern of zonal wind and Outgoing Longwave Radiation (OLR) by the time of MJO was active and to find the time when MJO was active using RMM1 and RMM2 index. Additionally, to knowing the characteristic of correlation between MJO signal and zonal wind in Padang. This research used secondary data in velocity of zonal wind form, height 850 mb,  reanalysis OLR data and index realtime multivariate (RMM1 and RMM2). Data are analyzed by using a program Weight Wavelet Z-transform (WWZ) and surfer 7 to see the patern and timing of the appearance MJO and characteristics of the connection MJO index RMM1 and RMM2 with 850mb zonal wind with simple regresion analysis and value of coeffisien determination (R2). The results showed that 850 mb zonal wind speed ranging from 5 m/s which suports to make formation of rain clouds and the carrier is evidenced by the low value of OLR as charactheristics of the MJO. The emergence of an active MJO phase 4, the impact caused by the emergence of the active phase of the MJO is a low wind speed and high rainfall during the propagation of the Indian ocean to the Pacific ocean that occured in the City of Padang. Time MJO emergence occured 19 time during 2010-2015. A highly significant connection between zonal wind and RMM1 and RMM2 850 with confidence interval 97%, and the effect on rainfall during the MJO is active in the City of Padang